Pengaruh Store Atmosphere dan Media Sosial Terhadap Keputusan Pembelian pada Mahatir Store - Arif Rahman; Muhajirin Muhajirin; M Syukur Dwiriansyah (PT Ilmu Data Indonesia, 2024)
Mahathir store is a store that sells cellphone accessories. At present it is much loved by the people of Bima City because it sells various types of cellphone and accessories needs which are more affordable compared to other stores. Apart from selling new cellphones, the Mahathir Store also sells various kinds of second hand cellphones which are guaranteed service forever. There are several ways that the Mahathir Store does to attracting potential customers from giving large discounts to customers, providing official guarantees with a long period of time, making it easier for customers to make purchases with the cash on delivery (COD) system or shopping online, and providing trade-in services, up to credit purchases , behind these advantages, the Mahathir Store also has a downside, such as a cramped store atmosphere that will impact consumers and prospective consumers who shop at Mahathir Store stores. The aim of this research is to determine whether there is an influence of Store Atmosphere and Social Media on purchases at the Mahathir Store. The population in this study is all the people of Bima City who shop at the Mahatir Store with a total sample of 96 people. The data analysis techniques used are validity and reliability tests, classical assumption test, multiple linear regression test, multiple correlation coefficient test, determination test, T test and F test. Based on the results of statistical analysis the t test variable store atmosphere influences purchasing decisions at the Mahathir Store (Study on consumers in the city of Bima). Likewise, social media variables influence purchasing decisions at the Mahathir Store (study of Kota Bima consumers). Based on the results of the f test, it is known that the Store Atmosphere and Social Media variables influence consumer purchasing decisions at the Mahathir Store